2006
DOI: 10.1007/s11199-006-9122-z
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Involvement with School-aged Children in Brazilian Families: Association with Childhood Competence

Abstract: Thirty-eight middle-to lower-income Brazilian fathers in two-parent families provided estimates of different dimensions of their involvement with their school-aged children, assessed children's social competence, and rated their beliefs on family roles. Analyses showed that fathers and mothers spent similar amounts of time in different activities with children, but did differ in didactic interactions, their responsibility for, and actually disciplining children. There were no significant differences in partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Reviewing findings from previously conducted studies on fathers, Pleck and Masciadrelli (2004) noted tremendous variation in men's levels of involvement across cultures. This variability is reflected in fathers' higher levels of participation with children per day in a U.S. representative sample (73% of the time mothers spent; Yeung et al, 2001), Canadian families (74%; Zuzanek, 2000), Malay and Chinese Malaysians (71%; Noor, 1999), and Brazilian families (77%; Benetti & Roopnarine, 2006). By contrast, lower levels of involvement were observed in Kadazan (20%; Hossain et al, 2007), Chippewa/Ojibwa Indian families (31%; Radin et al, 1993; Williams et al, 1996), African American (40%; Hossain & Roopnarine, 1993), Latino (37%; Roopnarine & Ahmeduzzaman, 1993), Malay (32%; Hossain et al, 2005), and Thai families (36%; Tulananda & Roopnarine, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing findings from previously conducted studies on fathers, Pleck and Masciadrelli (2004) noted tremendous variation in men's levels of involvement across cultures. This variability is reflected in fathers' higher levels of participation with children per day in a U.S. representative sample (73% of the time mothers spent; Yeung et al, 2001), Canadian families (74%; Zuzanek, 2000), Malay and Chinese Malaysians (71%; Noor, 1999), and Brazilian families (77%; Benetti & Roopnarine, 2006). By contrast, lower levels of involvement were observed in Kadazan (20%; Hossain et al, 2007), Chippewa/Ojibwa Indian families (31%; Radin et al, 1993; Williams et al, 1996), African American (40%; Hossain & Roopnarine, 1993), Latino (37%; Roopnarine & Ahmeduzzaman, 1993), Malay (32%; Hossain et al, 2005), and Thai families (36%; Tulananda & Roopnarine, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Only recently have studies across cultures and ethnicities of parent-child socialization been examined in order to understand the diversity of the roles mothers and fathers assume in the family (Benetti & Roopnarine, 2006;Biller, 1993;Bozett & Hanson, 1991;Flouri, 2005;Hossain, Roopnarine, Ismail, Hashmi, & Sombuling, 2007;Parke, 1996;Roopnarine & Carter, 1992). For years, a traditional two-parent family consisted of the mother assuming the role of the primary caregiver, staying at home and tending to the needs of the children, while the father assumed the role of working full-time outside the home.…”
mentioning
confidence: 99%
“…Likewise, data suggest that mothers’ proportional involvement in physical care of children exceeds that of fathers in the United States, Canada, and the Netherlands (78%, 66.8%, and 39.1% of mothers’ time investment, respectively; Pleck & Masciadrelli, 2004). Other studies indicate lower levels of physical care by fathers, when compared with mothers, in Malaysian (Hossain et al, 2005), Japanese (Sôrifu, 1997), East Indian (Suppal, Roopnarine, Buesig, & Bennett, 1996), Brazilian (Benetti & Roopnarine, 2006), and Jamaican (Roopnarine et al, 1995) families. Despite these well-documented discrepancies, far less is known about potential changes in the distribution of child care and household labor among families who have migrated from technologically developing to technologically developed societies.…”
Section: Previous Research On English-speaking Caribbean Immigrant Fa...mentioning
confidence: 99%
“…The results showed that father involvement in parenting can be done using 5 approaches: 1) Social engagement (teaching children to interact with others and helping train children's memory), 2) Didactic engagement (helping to improve children's cognition, teaching school assignments, helps learn communication, and helps to concentrate), 3) Engagement in a discipline (responsible for disciplining children and helping children to be able to manage their studies well), 4) Engagement in affection (teaching children skills to support the learning process and help express ideas), 5) Parental caring (easy to contact when working and being near children at home) and 6) Parental responsibility (coming to meetings at school, making/arranging schedules at school) (Benetti & Roopnarine, 2006). Examples of some of the subject's responses through interviews conducted are as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Hawkins & Palkovits (1999) emphasize the importance of involvement manifestations that include affective, psychological, cognitive, economic, ethical, and spiritual aspects. Benetti & Roopnarine (2006) developed the theory of lamb, et al (parental engagement, parental availability, and parental responsibility by designing a measuring tool called the Parental Involvement Index, consisting of aspects: 1) Social engagement (teaching children to interact with others) others and help train children's memory), 2) Didactic engagement (help improve children's cognition, teach school assignments, help learn communication, and help concentration), 3) Engagement in discipline (responsible for disciplining children and helping children to be able to good learning management), 4) Engagement in affection (teaching children skills to support the learning process and help express ideas), 5) Parental caring (easy to contact when working and being near children at home), and 6) Parental responsibility ( come to meetings at school, make/arrange schedules at school).…”
Section: Father's Involvement In Parentingmentioning
confidence: 99%